A service quality evaluation scale for the hospitality sector: dimensions, attributes and behavioural intentions - Salazar, A.; Costa, J.; Rita, P. (Worldwide Hospitality and Tourism Themes, 2010)
Purpose: The purpose of this paper is to present a scale for service quality evaluation in the hospitality sector. This scale has two aims: to assess the dimensions and attributes consumers use when evaluating the quality of the service provided by hotels, and to determine what influence service quality perceptions have on consumer behaviour, namely on customer intentions to return and to recommend the hotel. Design/methodology/approach: The methodology used to develop the scale was divided into three stages: first, two well-known models (SERVQUAL with direct formulation and SERPERF) were tested in 32 hotels, through 532 questionnaires. As these models were not conclusive, a second phase took place: 109 in-depth interviews were conducted to assess the relevant factors or attributes for consumers during a hotel stay, both for the holiday and business segments. Based on the results of the interviews, a questionnaire was designed to evaluate service quality provided by four and five star hotels. On this third phase, a sample of 257 respondents/hotel customers was achieved. Findings: The main results point to the existence of five dimensions: room (tangibles and service); feelings; restaurant service; tangibles (location, exterior and restaurant) and reception, explaining 56,1 per cent of the consumers' service quality evaluation. Another finding points out the existence of a stronger relationship between service quality perceptions and the intention to recommend the hotel (74,8 per cent) than the intention to return to the hotel (55,9 per cent). Originality/value: Based on the knowledge of the relative importance of the attributes consumers use when evaluating the service provided by four and five stars hotels, the relevant influence emotions have on consumers' service quality evaluation and the influence service quality perceptions have on behavioural intentions, several recommendations to managers are made, both in terms of managing the hotel, as well as tourist destinations.